2018
DOI: 10.21010/ajtcamv15i2.2
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Compositions and Biological Properties of Essential Oils From Zanthoxylum Rhetsa (Roxb.) Dc and Zanthoxylum Limonella Alston

Abstract: Background: Zanthoxylum rhetsa (Roxb.) DC and Zanthoxylum limonella Alston are spices for flavouring in indigenous Thai food. They are traditionally used as an aromatic, astringent, antimicrobial, antiseptic and antidiabetic agent. The purpose of this study is to examine their chemical compositions and evaluate antibacterial, antioxidant and anticancer properties of the essential oils. Materials and Methods: The essential oils of Z. rhetsa and Z. limonella were analysed for phytochemical constituents by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…The observed GC-MS chemical pro les of every EO were well-matched with those reported in a previous study. Namely, the percentage of geranial, the major chemical constituent of C. citratus EO observed in this study, was 46.33%, while papers by Aungtikun et al 28 , Soonwera and Sittichok 24 , and Chauhan et al 34 reported the percentage geranial at 42.40-49.69% of the EO chemical pro le; in addition, the observed major constituent of C. verum EO was cinnamaldehyde at 75.23%, well-matched with 73.21% of the chemical pro le reported by Aungtikun and Soonwera 27 and with 74.49% reported by Li et al 31 , and lower than 90.17% reported by Chansang et al 35 ; the observed major constituent of E. globulus EO was 1,8-cineole, at 45.82%, well-matched with 42.60-44.54% of the chemical pro le reported by Soonwera and Sittichok 24 and Cotchakaew and Soonwera 36 ; the observed major constituent of I. verum EO was trans-anethole, at 92.24%, well-matched with 88.32-94.0% of the chemical pro le reported by Aungtikun et al 28 and Junior et al 37 ; and the observed major constituent of Z. limonella EO was limonene, at 28.13%, slightly higher than 18.62% reported by Imphat and Woottisin 38 , and lower than 43.63% reported by Charoensup et al 26 , and 57.94% reported by Wongkattiya et al 39 . Nevertheless, there were some slight discrepancies, such as the yield and percentage in the chemical pro le of the major constituents of I. verum and Z. limonella EOs.…”
Section: Discussionsupporting
confidence: 82%
“…The observed GC-MS chemical pro les of every EO were well-matched with those reported in a previous study. Namely, the percentage of geranial, the major chemical constituent of C. citratus EO observed in this study, was 46.33%, while papers by Aungtikun et al 28 , Soonwera and Sittichok 24 , and Chauhan et al 34 reported the percentage geranial at 42.40-49.69% of the EO chemical pro le; in addition, the observed major constituent of C. verum EO was cinnamaldehyde at 75.23%, well-matched with 73.21% of the chemical pro le reported by Aungtikun and Soonwera 27 and with 74.49% reported by Li et al 31 , and lower than 90.17% reported by Chansang et al 35 ; the observed major constituent of E. globulus EO was 1,8-cineole, at 45.82%, well-matched with 42.60-44.54% of the chemical pro le reported by Soonwera and Sittichok 24 and Cotchakaew and Soonwera 36 ; the observed major constituent of I. verum EO was trans-anethole, at 92.24%, well-matched with 88.32-94.0% of the chemical pro le reported by Aungtikun et al 28 and Junior et al 37 ; and the observed major constituent of Z. limonella EO was limonene, at 28.13%, slightly higher than 18.62% reported by Imphat and Woottisin 38 , and lower than 43.63% reported by Charoensup et al 26 , and 57.94% reported by Wongkattiya et al 39 . Nevertheless, there were some slight discrepancies, such as the yield and percentage in the chemical pro le of the major constituents of I. verum and Z. limonella EOs.…”
Section: Discussionsupporting
confidence: 82%
“…To be able to compare the experimental outcomes of this study meaningfully with those of other studies on EO and insect pests, the composition of the extracted EOs in this study must be the same or nearly the same as the composition of the reported EOs in the literature. Therefore, the chemical compositions of all extracted essential oils were determined by GC-MS to ascertain that they were the same as those reported previously ( Aungtikun et al., 2021 ; Wongkattiya et al., 2018 ). It was observed that the major constituent of I .…”
Section: Discussionmentioning
confidence: 99%
“…(2020) reported a lower percentage of trans-anethole (88.6%) in the total composition. This discrepancy could be due to many factors, e.g., different geographical areas of the farms where these plants had been grown ( Wongkattiya et al., 2018 ), different soil and fertilizer conditions, and different harvest times (i.e., harvesting the plants at which growth stage and season) ( Wongkattiya et al., 2018 ; Aungtikun and Soonwera, 2021 ). For Z .…”
Section: Discussionmentioning
confidence: 99%
“…Pham et al suggested that terpinen-4-ol that is the main active constituent in Z. rhetsa pericarp EOs had the ability to inhibit stomach and intestine diseases [11]. Some other studies have also shown that essential oils obtained from plants exhibited potential antibacterial and antifungal activities [20][21][22].…”
Section: Antimicrobial Activitymentioning
confidence: 99%